Lactobacillus and bifidobacterium in irritable bowel syndrome: symptom responses and relationship to cytokine profiles - O'Mahony, Liam; McCarthy, Jane; Kelly, Peter; Hurley, George; Luo, Fangyi; Chen, Kersang; O'Sullivan, Gerald C; Kiely, Barry; Collins, J Kevin; Shanahan, Fergus; Quigley, Eamonn M M (Gastroenterology (New York, N.Y. 1943), 2005)
The aim of this study was to compare the response of symptoms and cytokine ratios in irritable bowel syndrome (IBS) with ingestion of probiotic preparations containing a lactobacillus or bifidobacterium strain. Seventy-seven subjects with IBS were randomized to receive either Lactobacillus salivarius UCC4331 or Bifidobacterium infantis 35624, each in a dose of 1 x 10 10 live bacterial cells in a malted milk drink, or the malted milk drink alone as placebo for 8 weeks. The cardinal symptoms of IBS were recorded on a daily basis and assessed each week. Quality of life assessment, stool microbiologic studies, and blood sampling for estimation of peripheral blood mononuclear cell release of the cytokines interleukin (IL)-10 and IL-12 were performed at the beginning and at the end of the treatment phase. For all symptoms, with the exception of bowel movement frequency and consistency, those randomized to B infantis 35624 experienced a greater reduction in symptom scores; composite and individual scores for abdominal pain/discomfort, bloating/distention, and bowel movement difficulty were significantly lower than for placebo for those randomized to B infantis 35624 for most weeks of the treatment phase. At baseline, patients with IBS demonstrated an abnormal IL-10/IL-12 ratio, indicative of a proinflammatory, Th-1 state. This ratio was normalized by B infantis 35624 feeding alone. B infantis 35624 alleviates symptoms in IBS; this symptomatic response was associated with normalization of the ratio of an anti-inflammatory to a proinflammatory cytokine, suggesting an immune-modulating role for this organism, in this disorder.